(untitled) (International Journal of Innovative Technologies in Economy, 2018)
In the final analysis the profit and profitability are most important indicators of the effective management. They most fully characterize economic results of the enterprise of the production and the management in general. The effect presents the result of carrying out activities aimed at improving production, entrepreneurial activity and the organization as a whole. The control effect consists of three components: - economic effect, i.e. the kind of effect that has a directly value form, that is, measured in monetary or natural meters; - socio-economic effect, which has a complex combination of economic benefits and social security - stability and tranquility, for example, improving working conditions, reducing the level of occupational morbidity (under certain conditions, can be converted into a normal economic effect); - social effect, i.e. effect, which can not be practically converted into economic, for example, prevention of social conflict, etc. [1].